2017
DOI: 10.1021/acs.iecr.7b01120
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Salts Supplementation on Xylitol Production by Debaryomyces hansenii Using a Synthetic Medium or Corncob Hemicellulosic Hydrolyzates and Further Scaled Up

Abstract: The synergic effect of eight salts on D-xylose to xylitol bioconversion by Debaryomyces hansenii NRRL Y-7426 was optimized through a central composite design (CCD) in shaker flasks. Optima conditions were then assayed using detoxified corncob hemicellulosic hydrolyzates as the carbon source, increasing the fermentative parameters to Q P = 0.118 g/L•h and Y P/S = 0.45 g/g from Q P = 0.101 g/L•h and Y P/S = 0.39 g/g (without supplementation). Finally, the process was successfully scaled up to a 50 L Braun Biosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The F-value (Fischer variance ratio) of the computed model was 122.15 and the p-value of < 0.0001, which implies p < 0.05 for regression model equation confirmed that the quadratic model fit well to the experimental results. The lack of fit value of 3.27 implied that the model’s variables significantly correlated with process response which was xylitol production [ 42 ]. Also, the difference between adjusted R 2 (0.9838) and predicted R 2 (0.9569) in the current study was less than 0.20, indicating that the model was reliable (Additional file 2 : Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The F-value (Fischer variance ratio) of the computed model was 122.15 and the p-value of < 0.0001, which implies p < 0.05 for regression model equation confirmed that the quadratic model fit well to the experimental results. The lack of fit value of 3.27 implied that the model’s variables significantly correlated with process response which was xylitol production [ 42 ]. Also, the difference between adjusted R 2 (0.9838) and predicted R 2 (0.9569) in the current study was less than 0.20, indicating that the model was reliable (Additional file 2 : Table S2).…”
Section: Resultsmentioning
confidence: 99%